Preparation and application of powder coating for anti-corrosion steel pipe for conveying seawater

By adopting a three-layer powder coating system, combined with epoxy resin, maleic anhydride grafted polyethylene and polytetrafluoroethylene, the problems of low adhesion and poor wear resistance of steel pipe anti-corrosion coating in the prior art are solved, and higher adhesion and wear resistance are achieved, and the service life of steel pipes is extended.

CN119799129APending Publication Date: 2025-04-11SHANDONG DONGHONG PIPE IND

Patent Information

Application Number
CN202510056743.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art has problems such as low coating adhesion, poor wear resistance, and susceptible to seawater corrosion and silt erosion in the anti-corrosion of seawater conveying steel pipes using liquid coatings, resulting in a shortening of the service life of the steel pipe.

Method used

A three-layer structure powder coating system is adopted. The bottom layer is made of epoxy resin as the main film-forming substance, the middle layer is made of epoxy powder and maleic anhydride grafted polyethylene powder as the main components, and the top layer is made of maleic anhydride grafted polyethylene, ultra-high molecular weight polyethylene, and polytetrafluoroethylene as the main substance. Through the combination of base powder, intermediate powder and flour, the adhesion, wear resistance and scratch resistance of the coating are enhanced.

Benefits of technology

It significantly improves the adhesion and wear resistance of the steel pipe surface coating, reduces the impact of seawater and silt corrosion and erosion on the coating, and extends the service life of the steel pipe.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005241651500000151
    Figure BDA0005241651500000151
  • Figure BDA0005241651500000161
    Figure BDA0005241651500000161
  • Figure BDA0005241651500000162
    Figure BDA0005241651500000162
Patent Text Reader

Abstract

The invention belongs to the technical field of coatings, and provides preparation and application of a powder coating for an anti-corrosion steel pipe for conveying seawater. Comprising base flour, intermediate flour and flour, the bottom layer is a powder coating with epoxy resin as a main film forming substance, the middle layer is a powder coating with epoxy powder and maleic anhydride grafted polyethylene powder as main components, and the surface layer is a powder coating with maleic anhydride grafted polyethylene, ultra-high molecular weight polyethylene and polytetrafluoroethylene as main substances. The problem that the steel pipe is not resistant to seawater corrosion and wear in the seawater conveying process is innovatively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to the preparation and application of a powder coating for an anti-corrosion steel pipe for conveying seawater. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] 71% of the earth's surface is covered by water, but 96.5% of it is seawater. The fresh water available to humans only accounts for 0.77% of the world's total water. The extensive use of seawater has become the main way to solve the shortage of fresh water in the 21st century. Seawater utilization includes direct use of seawater, seawater desalination and comprehensive use of seawater, as well as seawater agriculture. In seawater desalination projects, thermal power plants, and nuclear power plants, seawater cooling projects all require long-distance pipelines to introduce seawater into related equipment for use. At present, most long-distance pipelines for transporting seawater are steel pipes. In terms of corrosion protection of steel pipes, coating protection is widely used due to its advantages such as simple construction, low cost, and good effect. However, the corrosive environment of seawater is very harsh. On the one hand, ordinary liquid coating materials release small molecules due to solvent volatilization or self-cross-linking reaction, causing the coating itself to have tiny pores. Small molecules such as chloride ions in seawater can penetrate into the surface of the substrate and cause corrosion. On the other hand, due to the large amount of sediment contained in the seawater during transportation, ordinary liquid coating materials have poor wear resistance and are subject to erosion and corrosion during use. The coating will experience blistering, poor adhesion, and shedding within a short service life, which seriously affects the anti-corrosion effect and shortens the service life of the steel pipe.

[0004] The patent with publication number CN110205000A discloses a phenolic epoxy powder coating for corrosion protection in desalination pipelines. The phenolic epoxy powder coating is composed of two components, A and B. The A component includes: 30-50 parts of epoxy resin, 20-35 parts of pigments and fillers, 3-12 parts of additives, and 5-15 parts of solvents; the B component includes: 40-60 parts of amine curing agents, 2-10 parts of solvents, and 0.5-3 parts of coupling agents. The coating in the patent only forms a single coating, and the dry adhesion of the coating is 8.2MPa, which is low in adhesion and is not conducive to long-term corrosion protection.

[0005] The patent with the publication number CN113845844A discloses a composite anti-corrosion and anti-fouling treatment process for marine facilities, in which a composite coating is formed by a composite spraying treatment on the surface of the marine facility structure, and the composite coating includes a bottom layer, an intermediate layer and a surface layer, wherein the bottom layer is an epoxy resin coating, the intermediate layer is a polyurea coating, and the surface layer is a coating formed by a nano antifouling coating. Although the process combines the advantages of polyurea treatment and nano antifouling coating, the process uses liquid coating, and the surface must be dry before construction between each layer, the construction period is long, and each layer is independently arranged, and the adhesion between layers is low.

[0006] Patent number CN116716020B discloses a seawater corrosion-resistant anticorrosive powder material, including base powder, middle powder and flour powder, with a three-layer structure of a powder coating with epoxy resin as the main film-forming substance at the bottom layer, a powder coating with polyvinylidene chloride resin as the main film-forming substance at the middle layer, and a powder coating with polyethylene as the main film-forming substance at the surface layer. The high barrier properties of polyvinylidene chloride resin and the wear resistance of low-density polyethylene resin at the surface layer are utilized to solve the problem of steel pipes being not resistant to seawater corrosion and having a short service life during the transportation of seawater. However, the adhesion and wear resistance between the powder system and the metal are both low, and the coating is easily peeled off and erosion corrosion occurs during use. Summary of the invention

[0007] In order to solve the above problems, the present invention provides a preparation and application of a powder coating for an anti-corrosion steel pipe for conveying seawater. The anti-corrosion powder material provided by the present invention can be coated on a steel pipe for conveying seawater, and has the characteristics of extremely strong adhesion, extremely high wear resistance and scratch resistance.

[0008] In order to achieve the above object, the present invention adopts the following technical solution:

[0009] A first aspect of the present invention provides a powder coating for an anticorrosive steel pipe for conveying seawater, comprising: a base powder, an intermediate powder and a flour powder;

[0010] The base powder is composed of the following raw materials in parts by weight: 20-30 parts of bisphenol A epoxy resin, 20-30 parts of phenolic epoxy resin, 5-10 parts of isocyanate modified epoxy resin, 15-25 parts of phenolic curing agent, 2-5 parts of polyvinyl butyral, 0.5-2 parts of accelerator, 0.5-2 parts of coupling agent, 0.5-2 parts of nano silicon dioxide, 10-20 parts of color filler, 0.5-1 parts of leveling agent, and 0.5-1 parts of defoaming agent;

[0011] The intermediate powder is a mixture of two components A and B, wherein component A is the base powder, and component B is composed of the following raw materials in parts by weight: 50-70 parts of maleic anhydride grafted polyethylene, 5-15 parts of maleic anhydride grafted polyethylene wax, 5-15 parts of polyvinyl butyral, and 0.5-1 part of defoaming agent;

[0012] The flour is composed of the following raw materials in parts by weight: 30-60 parts of maleic anhydride grafted polyethylene, 5-10 parts of ultra-high molecular weight polyethylene, 5-10 parts of maleic anhydride grafted polyethylene wax, 1-10 parts of a compatibilizer, 10-20 parts of polytetrafluoroethylene, 10-20 parts of fused silica powder, 1-5 parts of a pigment, and 0.2-1 parts of an antioxidant.

[0013] The present invention develops an anti-corrosion powder material with high adhesion, excellent cathode stripping resistance, good wear resistance and excellent scratch resistance, which can meet the use requirements of steel pipes for conveying seawater.

[0014] In some embodiments, the particle size of the base powder is 60 mesh to 180 mesh.

[0015] In some embodiments, the softening point of the bisphenol A epoxy resin in the base powder is 85° C.-130° C., including one-step epoxy resin, two-step epoxy resin, or a combination of several thereof.

[0016] In some embodiments, the phenolic epoxy resin in the base powder includes one or a combination of commercially available DER672U from Dow Chemical, Amanda1168, Amanda1177HTM, Amanda1178HTX from Daqing Qinglu Langrun Technology Co., Ltd., NPCN-702 from Nanya Electronics, and 704 resin from Baling Petrochemical.

[0017] In some embodiments, the isocyanate-modified epoxy resin in the primer includes commercially available AER4004 and AER4152 from Asahi Chemical.

[0018] In some embodiments, the phenolic curing agent in the base powder includes one or a combination of KD404, KD405, KD406 from Gukdu, South Korea, V-2083, V-2081, V-2059 from Jinchen, Shaanxi, 969 series and 979 series curing agents from Qinglu, Daqing.

[0019] In some embodiments, the polyvinyl butyral in the base powder and the intermediate powder includes commercially available products such as SD-2 and SD-3 from Tianjin Everbright Bingfeng New Materials Technology Co., Ltd., and TB-8 and TB-12 from Yingkou Tianyuan Polymer Materials Co., Ltd.

[0020] In some embodiments, the promoter is an imidazole or cyclic amidine substance, preferably, at least one selected from 2-methylimidazole and 2-isopropylimidazole;

[0021] In some embodiments, the coupling agent is a powder coupling agent containing epoxy groups; preferably, the coupling agent includes one or a combination of PCA-302A and PCA-302E produced by Nanjing Nengde Company.

[0022] In some embodiments, the nano-silica in the base powder is a hydrophobic fumed silica product, commonly used ones include commercially available Evonik R-972, R-974, etc.

[0023] In some embodiments, the pigment filler is selected from at least one of titanium dioxide, phthalocyanine blue, phthalocyanine green, medium chrome yellow, DPP red, permanent red, permanent violet, ultramarine, nano barium sulfate, nano calcium carbonate, nano silicon powder, nano wollastonite powder, nano feldspar powder, and mica powder;

[0024] In some embodiments, the leveling agent is an acrylic leveling agent; preferably, the leveling agent includes one or a combination of several of PV88 from Ningbo Nanhai, L88 from Wuhan Yincai, WK538 from Ningbo Weikai Chemical, etc.

[0025] In some embodiments, the defoaming agent is a benzoin product. Preferably, it includes one or more of pure benzoin and anti-yellowing benzoin. More preferably, it includes commercially available products such as L307 from Wuhan Yincai, benzoin from Nanhai Chemical, and WK307 from Ningbo Weikai.

[0026] In some embodiments, the mass ratio of component A to component B is 1:1-1.5.

[0027] In some embodiments, the particle size of the B component is 60 mesh to 100 mesh.

[0028] In some embodiments, the maleic anhydride grafted polyethylene material in the intermediate powder component B has a melt index of 2 g / 10 min-20 g / 10 min at 190° C. and 2.16 kg, such as commercially available products such as EN660, EN360, F-1, and F-2 of Donghong Pipe Industry.

[0029] In some embodiments, the maleic anhydride grafted polyethylene wax in the intermediate powder component B includes commercially available PEMA4351 from Klein and 1105A from Mitsui Chemicals.

[0030] In some embodiments, the polyvinyl butyral in the intermediate powder component B includes commercially available products such as SD-2 and SD-3 from Tianjin Everbright Bingfeng New Materials Technology Co., Ltd., and TB-8 and TB-12 from Yingkou Tianyuan Polymer Materials Co., Ltd.

[0031] In some embodiments, the particle size of the flour is 40 mesh to 100 mesh.

[0032] In some embodiments, the maleic anhydride grafted polyethylene in the flour is a product having a melt index of 2 g / 10 min-20 g / 10 min at 190° C. and 2.16 kg, such as commercially available products such as EN660, EN360, F-1, and F-2 of Donghong Pipe Industry.

[0033] In some embodiments, the ultra-high molecular weight polyethylene in the flour is VH245 or VH095 produced by Korea Petrochemical.

[0034] In some embodiments, the maleic anhydride grafted polyethylene wax in the flour includes commercially available PEMA4351 from Klein and 1105A from Mitsui Chemicals.

[0035] In some embodiments, the compatibilizer is tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer resin; preferably, it includes commercially available ACX-41, ACX-31, ACX-34 resins produced by Daikin Corporation of Japan.

[0036] In some embodiments, the polytetrafluoroethylene in the flour is a powdered product, including commercially available PTEF-0141 and PTEF-0121 from Nanjing Tianshi, A01 from Shenyang Tianyuxiang Micropowder Materials, and the like.

[0037] In some embodiments, the pigment is selected from at least one of carbon black, titanium dioxide, phthalocyanine blue, phthalocyanine green, medium chrome yellow, DPP red, permanent red, permanent violet, and ultramarine;

[0038] In some embodiments, the antioxidant is selected from at least one of antioxidant 215 , antioxidant 1010 , and antioxidant 168 .

[0039] The second aspect of the present invention provides a method for preparing the above-mentioned powder coating for anticorrosive steel pipes for conveying seawater, comprising:

[0040] The raw materials of the base powder are mixed evenly, extruded by twin screws, crushed by tableting, ground, and sieved to obtain the base powder;

[0041] The raw materials of component B are mixed evenly, extruded by twin screws, cooled, and pelletized; the pellets are low-temperature cooled, and the cooled pellets are ground into powder by ultra-low temperature grinding process, and sieved to obtain intermediate powder component B;

[0042] Mix component A and component B evenly to obtain intermediate powder;

[0043] The various raw materials of flour are mixed evenly, extruded by twin screws, cooled, and pelletized underwater; the pellets are cooled at low temperature, and the cooled pellets are ground into powder by ultra-low temperature grinding process, and sieved to obtain flour.

[0044] The third aspect of the present invention provides a coating process for the above-mentioned anticorrosive steel pipe powder coating for conveying seawater, comprising:

[0045] The steel pipe is preheated and derusted, then heated to rotate, and the base powder and the intermediate powder are sprayed on the inner and outer walls of the steel pipe in sequence. The steel pipe is placed in a heating furnace for melting while being kept in a rotating state, and then the steel pipe is taken out and flour is sprayed on the intermediate powder. Finally, the steel pipe is placed in a heating furnace for secondary heating while being kept in a rotating state, and then taken out and cooled naturally to obtain the product.

[0046] In some embodiments, after preheating and rust removal, the anchor mark depth on the surface of the steel pipe reaches 40-100 μm, and the surface rust removal grade reaches Sa2.5.

[0047] In some embodiments, the steel pipe is heated to 180°C-210°C after preheating and rust removal.

[0048] In some embodiments, a base powder having a thickness of 190-210 μm and an intermediate powder having a thickness of 190-210 μm are sprayed on the inner and outer walls of the steel pipe in sequence.

[0049] In some embodiments, the steel pipe is placed in a 230° C. heating furnace for melting and solidification for 10 min-20 min, and the steel pipe is taken out. At this time, the surface of the anti-corrosion layer on the inner and outer walls of the steel pipe is a rough surface.

[0050] In some embodiments, flour with a thickness of 270-330 μm is sprayed again outside the intermediate powder coating on the inner and outer walls of the steel pipe in a rotating state.

[0051] In some embodiments, the steel pipe is placed in a 230° C. heating furnace for melt leveling for 10 min to 20 min.

[0052] In some embodiments, the coated steel pipe is taken out from the heating furnace, and is naturally cooled to room temperature while being kept in a rotating state, thereby obtaining the target product, an anti-corrosion steel pipe capable of transporting seawater.

[0053] The fourth aspect of the present invention provides the application of the above powder coating in the field of marine engineering and steel pipe anti-corrosion, including: a seawater transport steel pipe, the inner and outer wall surfaces of the steel pipe are attached with a paint film, and the paint film is formed by the above anti-corrosion powder material.

[0054] Beneficial Effects of the Invention

[0055] (1) The present invention adopts a three-layer structure in which a powder coating with epoxy resin as the main film-forming substance as the bottom layer, a powder coating with epoxy powder and maleic anhydride grafted polyethylene powder as the main components as the middle layer, and a powder coating with maleic anhydride grafted polyethylene, ultra-high molecular weight polyethylene, and polytetrafluoroethylene as the main substances as the surface layer. This innovatively solves the problem that steel pipes are not resistant to seawater corrosion and wear during the process of transporting seawater.

[0056] (2) The addition of phenolic modified epoxy resin, isocyanate modified epoxy resin, polyvinyl butyral and other materials in the base powder of the present invention can play a synergistic role and greatly enhance the adhesion between the powder coating and the steel pipe. The nano-silicon dioxide added to the base powder can fill the pores of the powder coating, further enhancing the cathode stripping resistance and corrosion resistance of the base powder.

[0057] (3) The intermediate powder of the present invention mainly plays the role of bonding the base powder and flour. Two components A and B are used, and the A and B components are physically mixed evenly and sprayed on the base powder. The A component is consistent with the base powder and can form a good bonding force with the base powder. The maleic anhydride grafted polyethylene and maleic anhydride grafted polyethylene wax in the B component can react with the epoxy resin in the A component and the epoxy resin in the base powder, further enhancing the bonding force between the intermediate powder and the base powder. The maleic anhydride grafted polyethylene and maleic anhydride grafted polyethylene wax in the B component are consistent with the maleic anhydride grafted polyethylene and maleic anhydride grafted polyethylene wax in the flour, and can be well melt-bonded with the flour. On the other hand, the intermediate powder will form a rough surface during the film-forming process, further enhancing the bonding effect with the base powder and flour.

[0058] (4) The addition of ultra-high molecular weight polyethylene and polytetrafluoroethylene to the flour of the present invention can enhance the wear resistance and scratch resistance of the coating. The added maleic anhydride grafted polyethylene, compatibilizer, etc. can enhance the compatibility and binding force of the materials in the flour. The added maleic anhydride grafted polyethylene is used as a basic film-forming substance, and the added maleic anhydride grafted polyethylene wax is used to adjust the viscosity of the formula system.

[0059] (5) The anti-corrosion powder material prepared by the present invention is sprayed with three kinds of powders, namely base powder, middle powder and flour powder, on the surface of the steel pipe in sequence during use, and is formed in one step, with high production efficiency and easy promotion. DETAILED DESCRIPTION

[0060] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0061] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.

[0062] Example 1

[0063] Preparation of foundation powder:

[0064] Weigh 30 parts of Anhui Hengyuan bisphenol A epoxy resin HY905, 20 parts of Daqing Qinglu Langrun Technology Co., Ltd. phenolic epoxy resin Amanda1177HTM, 5 parts of Asahi Chemical's isocyanate modified epoxy resin AER4004, 15 parts of Shaanxi Jinchen's phenolic curing agent Shaanxi Jinchen's V-2083, 4 parts of Tianjin Everbright Bingfeng New Materials Technology Co., Ltd.'s polyvinyl butyral SD-2, 0.5 parts of accelerator 2-methylimidazole, 2 parts of Nanjing Nengde's coupling agent PCA-302A, 2 parts of Evonik's nano-silica R-972, 20 parts of pigments and fillers (titanium dioxide: phthalocyanine blue: barium sulfate = 2:1:12), 1 part of Wuhan Yincai's leveling agent L88, and 0.5 parts of Wuhan Yincai's defoaming agent L307;

[0065] The above raw materials were sequentially put into a tumble mixer and stirred for 10 minutes to make the raw materials evenly mixed, and then extruded through a twin-screw extruder with a set temperature of 105°C and an aspect ratio of 16:1. The extruded material was tableted and broken into flaky fragments through a water-cooled tablet press, and then ground through an ACM grinder. The powder was sieved through a 100-mesh screen to prepare a base powder.

[0066] Preparation of intermediate powder:

[0067] Component A is the foundation powder in Example 1;

[0068] Preparation of component B:

[0069] Weigh 70 parts of maleic anhydride grafted polyethylene F-1 (melt index of 15g / 10min at 190℃ and 2.16kg) produced by Donghong Pipe Industry, 15 parts of maleic anhydride grafted polyethylene wax PEMA4351 produced by Klein, 14 parts of polyvinyl butyral SD-2 produced by Tianjin Everbright Bingfeng New Materials Technology Co., Ltd., and 1 part of defoamer L307 produced by Wuhan Yincai, mix the above raw materials evenly in a high-speed mixer at room temperature, and prepare them into granular materials through a twin-screw extruder at 140-200℃, through melting, extrusion, cooling, and pelletizing processes. Put the granular materials into a cooling tank containing liquid nitrogen to cool down, and grind the liquid nitrogen-cooled particles into powder using an ultra-low temperature grinding process. The powder is sieved through an 80-mesh screen to obtain component B.

[0070] Add component A and component B in a mass ratio of 1:1 into a double cone mixer and mix for 15 minutes. After discharging from the double cone mixer, the intermediate powder is obtained.

[0071] Flour preparation:

[0072] Weigh 50 parts of maleic anhydride grafted polyethylene F-1 (melt index of 15g / 10min at 190℃ and 2.16kg) produced by Donghong Pipe Industry, 5 parts of ultra-high molecular weight polyethylene VH245 produced by Korea Petrochemical, 5 parts of maleic anhydride grafted polyethylene wax PEMA4351 produced by Klein, 10 parts of compatibilizer ACX-41 produced by Daikin Corporation of Japan, 10 parts of polytetrafluoroethylene PTEF-0141 produced by Nanjing Tianshi, 14.5 parts of fused silica powder, 5 parts of pigment (titanium dioxide: phthalocyanine blue), and 0.5 parts of antioxidant 215.

[0073] The above raw materials are mixed evenly in a high-speed mixer at room temperature, and passed through a twin-screw extruder at 140-200°C, and prepared into granular materials through melting, extrusion, cooling, and pelletizing processes. The granular materials are placed in a cooling tank containing liquid nitrogen for cooling, and the liquid nitrogen-cooled particles are ground into powder using an ultra-low temperature grinding process, and the powder is sieved through a 100-mesh screen to obtain flour.

[0074] Preparation of anti-corrosion steel pipe:

[0075] The steel pipe is preheated at 40℃ medium frequency to remove surface moisture, and then shot blasting is used to remove rust, so that the anchor pattern depth of the steel pipe surface reaches 40-100μm, and the surface rust removal level reaches Sa2.5. Then the rust-removed steel pipe is heated to 180℃, and the steel pipe is rotated by a mechanical device. A 200μm thick base powder and a 200μm thick intermediate powder are sprayed on the inner and outer walls of the steel pipe respectively, and the steel pipe is placed in a 230℃ heating furnace for melt solidification and leveling for 15 minutes. The steel pipe is taken out of the heating furnace. At this time, the surface of the anti-corrosion layer on the inner and outer walls of the steel pipe is rough. Spray 300μm thick flour while hot in the rotating state, and put the steel pipe into a 230℃ heating furnace for melt leveling for 15 minutes while keeping the rotation state, and then take out the steel pipe to cool naturally.

[0076] Comparative Example 1:

[0077] Only the foundation powder from Example 1 was used.

[0078] Preparation of anti-corrosion steel pipe:

[0079] The steel pipe is preheated at 40℃ medium frequency to remove surface moisture, and then shot blasted to remove rust, so that the anchor pattern depth of the steel pipe surface reaches 40-100μm, and the surface rust level reaches Sa2.5. The derusted steel pipe is then heated to 180℃, rotated by a mechanical device, and 700μm thick primer is sprayed on the inner and outer walls of the steel pipe, and the steel pipe is placed in a 230℃ heating furnace for melting, solidification and leveling for 15 minutes, and then the steel pipe is taken out and cooled naturally.

[0080] Comparative Example 2:

[0081] Only the intermediate powder from Example 1 was used.

[0082] Preparation of anti-corrosion steel pipe:

[0083] The steel pipe is preheated at 40℃ medium frequency to remove surface moisture, and then shot blasted to remove rust, so that the anchor pattern depth of the steel pipe surface reaches 40-100μm, and the surface rust level reaches Sa2.5. The derusted steel pipe is then heated to 180℃, rotated by a mechanical device, and 700μm thick intermediate powder is sprayed on the inner and outer walls of the steel pipe respectively. The steel pipe is placed in a heating furnace at 230℃ for melting, solidification and leveling for 15 minutes, and the steel pipe is taken out of the heating furnace and cooled naturally.

[0084] Comparative Example 3:

[0085] Only the flour from Example 1 was used.

[0086] Preparation of anti-corrosion steel pipe:

[0087] The steel pipe is preheated at 40℃ medium frequency to remove surface moisture, and then shot blasted to remove rust, so that the anchor pattern depth of the steel pipe surface reaches 40-100μm, and the surface rust level reaches Sa2.5. The derusted steel pipe is then heated to 230℃, rotated by a mechanical device, and 700μm thick flour is sprayed on the inner and outer walls of the steel pipe respectively. The steel pipe is placed in a 230℃ heating furnace while rotating for 15 minutes of melt leveling, and then the steel pipe is taken out and cooled naturally.

[0088] Comparative Example 4:

[0089] Only the base powder and face powder from Example 1 were used.

[0090] Preparation of anti-corrosion steel pipe:

[0091] The steel pipe is preheated at 40℃ medium frequency to remove surface moisture, and then shot blasting is used to remove rust, so that the anchor pattern depth of the steel pipe surface reaches 40-100μm, and the surface rust removal level reaches Sa2.5. Then the rust-removed steel pipe is heated to 180℃, and the steel pipe is rotated by a mechanical device. A 400μm thick base powder is sprayed on the inner and outer walls of the steel pipe respectively, and the steel pipe is placed in a 230℃ heating furnace for melting and solidification leveling for 15 minutes. The steel pipe is taken out of the heating furnace. At this time, the surface of the anti-corrosion layer on the inner and outer walls of the steel pipe is rough. Spray 300μm thick flour while rotating, and put the steel pipe into a 230℃ heating furnace for melting and leveling for 15 minutes while keeping the rotation state, and then take out the steel pipe to cool naturally.

[0092] Comparative Example 5:

[0093] The base powder and flour are consistent with those in Example 1.

[0094] Only the component B of the intermediate powder in Example 1 was used as the intermediate powder.

[0095] The preparation of the anti-corrosion steel pipe is consistent with that in Example 1.

[0096] Embodiment 2:

[0097] The base powder and the middle powder are the same as those in Example 1.

[0098] Flour preparation:

[0099] Weigh 45 parts of maleic anhydride grafted polyethylene F-1 (melt index of 15g / 10min at 190℃ and 2.16kg) produced by Donghong Pipe Industry, 5 parts of ultra-high molecular weight polyethylene VH245 produced by Korea Petrochemical, 5 parts of maleic anhydride grafted polyethylene wax PEMA4351 produced by Klein, 10 parts of compatibilizer ACX-41 produced by Daikin Corporation of Japan, 15 parts of polytetrafluoroethylene PTEF-0141 produced by Nanjing Tianshi, 14.5 parts of fused silica powder, 5 parts of pigment (titanium dioxide: phthalocyanine blue), and 0.5 parts of antioxidant 215.

[0100] The above raw materials are mixed evenly in a high-speed mixer at room temperature, and passed through a twin-screw extruder at 140-200°C, and prepared into granular materials through melting, extrusion, cooling, and pelletizing processes. The granular materials are placed in a cooling tank containing liquid nitrogen for cooling, and the liquid nitrogen-cooled particles are ground into powder using an ultra-low temperature grinding process, and the powder is sieved through a 100-mesh screen to obtain flour.

[0101] The preparation process of the anti-corrosion steel pipe is consistent with that in Example 1.

[0102] Comparative Example 6:

[0103] Preparation of foundation powder:

[0104] Weigh 50 parts of Anhui Hengyuan bisphenol A epoxy resin HY905, 5 parts of Asahi Chemical's isocyanate-modified epoxy resin AER4004, 15 parts of Shaanxi Jinchen's phenolic curing agent Shaanxi Jinchen's V-2083, 4 parts of Tianjin Everbright Bingfeng New Materials Technology Co., Ltd.'s polyvinyl butyral SD-2, 0.5 parts of accelerator 2-methylimidazole, 2 parts of Nanjing Nengde's coupling agent PCA-302A, 2 parts of Evonik's nano-silica R-972, 20 parts of pigments and fillers (titanium dioxide: phthalocyanine blue: barium sulfate = 2:1:12), 1 part of Wuhan Yincai's leveling agent L88, and 0.5 parts of Wuhan Yincai's defoaming agent L307;

[0105] The above raw materials were sequentially put into a tumble mixer and stirred for 10 minutes to make the raw materials evenly mixed, and then extruded through a twin-screw extruder with a set temperature of 105°C and an aspect ratio of 16:1. The extruded material was tableted and broken into flaky fragments through a water-cooled tablet press, and then ground through an ACM grinder. The powder was sieved through a 100-mesh screen to prepare a base powder.

[0106] The intermediate powder and flour are consistent with those in Example 2.

[0107] The preparation of the anti-corrosion steel pipe is consistent with that in Example 2.

[0108] Comparative Example 7:

[0109] Preparation of foundation powder:

[0110] Weigh 35 parts of Anhui Hengyuan bisphenol A epoxy resin HY905, 20 parts of Daqing Qinglu Langrun Technology Co., Ltd. phenolic epoxy resin Amanda1177HTM, 15 parts of Shaanxi Jinchen's phenolic curing agent Shaanxi Jinchen's V-2083, 4 parts of Tianjin Everbright Bingfeng New Materials Technology Co., Ltd.'s polyvinyl butyral SD-2, 0.5 parts of accelerator 2-methylimidazole, 2 parts of Nanjing Nengde's coupling agent PCA-302A, 2 parts of Evonik's nano-silica R-972, 20 parts of pigments and fillers (titanium dioxide: phthalocyanine blue: barium sulfate = 2:1:12), 1 part of Wuhan Yincai's leveling agent L88, and 0.5 parts of Wuhan Yincai's defoaming agent L307;

[0111] The above raw materials were sequentially put into a tumble mixer and stirred for 10 minutes to make the raw materials evenly mixed, and then extruded through a twin-screw extruder with a set temperature of 105°C and an aspect ratio of 16:1. The extruded material was tableted and broken into flaky fragments through a water-cooled tablet press, and then ground through an ACM grinder. The powder was sieved through a 100-mesh screen to prepare a base powder.

[0112] The intermediate powder and flour are consistent with those in Example 2.

[0113] The preparation of the anti-corrosion steel pipe is consistent with that in Example 2.

[0114] Comparative Example 8:

[0115] Preparation of foundation powder:

[0116] Weigh 34 parts of Anhui Hengyuan bisphenol A epoxy resin HY905, 20 parts of Daqing Qinglu Langrun Technology Co., Ltd. phenolic epoxy resin Amanda1177HTM, 5 parts of Asahi Chemical's isocyanate modified epoxy resin AER4004, 15 parts of Shaanxi Jinchen's phenolic curing agent Shaanxi Jinchen's V-2083, 0.5 parts of accelerator 2-methylimidazole, 2 parts of Nanjing Nengde's coupling agent PCA-302A, 2 parts of Evonik's nano-silica R-972, 20 parts of pigments and fillers (titanium dioxide: phthalocyanine blue: barium sulfate = 2:1:12), 1 part of Wuhan Yincai's leveling agent L88, and 0.5 parts of Wuhan Yincai's defoaming agent L307;

[0117] The above raw materials were sequentially put into a tumble mixer and stirred for 10 minutes to make the raw materials evenly mixed, and then extruded through a twin-screw extruder with a set temperature of 105°C and an aspect ratio of 16:1. The extruded material was tableted and broken into flaky fragments through a water-cooled tablet press, and then ground through an ACM grinder. The powder was sieved through a 100-mesh screen to prepare a base powder.

[0118] The intermediate powder and flour are consistent with those in Example 2.

[0119] The preparation of the anti-corrosion steel pipe is consistent with that in Example 2.

[0120] Comparative Example 9:

[0121] Preparation of foundation powder:

[0122] Weigh 32 parts of Anhui Hengyuan bisphenol A epoxy resin HY905, 20 parts of Daqing Qinglu Langrun Technology Co., Ltd. phenolic epoxy resin Amanda1177HTM, 5 parts of Asahi Chemical's isocyanate modified epoxy resin AER4004, 15 parts of Shaanxi Jinchen's phenolic curing agent Shaanxi Jinchen's V-2083, 4 parts of Tianjin Everbright Bingfeng New Materials Technology Co., Ltd.'s polyvinyl butyral SD-2, 0.5 parts of accelerator 2-methylimidazole, 2 parts of Nanjing Nengde's coupling agent PCA-302A, 20 parts of pigments and fillers (titanium dioxide: phthalocyanine blue: barium sulfate = 2:1:12), 1 part of Wuhan Yincai's leveling agent L88, and 0.5 parts of Wuhan Yincai's defoaming agent L307;

[0123] The above raw materials were sequentially put into a tumble mixer and stirred for 10 minutes to make the raw materials evenly mixed, and then extruded through a twin-screw extruder with a set temperature of 105°C and an aspect ratio of 16:1. The extruded material was tableted and broken into flaky fragments through a water-cooled tablet press, and then ground through an ACM grinder. The powder was sieved through a 100-mesh screen to prepare a base powder.

[0124] The intermediate powder and flour are consistent with those in Example 2.

[0125] The preparation of the anti-corrosion steel pipe is consistent with that in Example 2.

[0126] Embodiment 3:

[0127] The base powder and the middle powder are the same as those in Example 1.

[0128] Flour preparation:

[0129] Weigh respectively 45 parts of maleic anhydride grafted polyethylene F-1 (melt index of 15g / 10min at 190℃ and 2.16kg) produced by Donghong Pipe Industry, 10 parts of ultra-high molecular weight polyethylene VH245 of Korea Petrochemical, 5 parts of maleic anhydride grafted polyethylene wax PEMA4351 of Klein, 10 parts of compatibilizer ACX-41 of Daikin Corporation of Japan, 10 parts of polytetrafluoroethylene PTEF-0141 of Nanjing Tianshi, 14.5 parts of fused silica powder, 5 parts of pigment (titanium dioxide: phthalocyanine blue), and 0.5 parts of antioxidant 215.

[0130] The above raw materials are mixed evenly in a high-speed mixer at room temperature, and passed through a twin-screw extruder at 140-200°C, and prepared into granular materials through melting, extrusion, cooling, and pelletizing processes. The granular materials are placed in a cooling tank containing liquid nitrogen for cooling, and the liquid nitrogen-cooled particles are ground into powder using an ultra-low temperature grinding process, and the powder is sieved through a 100-mesh screen to obtain flour.

[0131] The preparation process of the anti-corrosion steel pipe is consistent with that in Example 1.

[0132] Detection method:

[0133] 1. Adhesion test: Use the pull-out method in GB / T 5210-2006 to test the adhesion between the base powder and the steel pipe, the adhesion between the base powder and the middle powder, the adhesion between the middle powder and the flour, the adhesion between the middle powder and the steel pipe, and the adhesion between the flour and the steel pipe.

[0134] 2. Wear resistance: Use the GB / T1768-2006 rotating rubber grinding wheel method, use a CS10 grinding wheel, rotate 1000 times under a load of 1kg to test the wear resistance of the coating.

[0135] 3. Scratch resistance: The test method in SY / T4113.1-2018 is adopted and the test is carried out with a weight of 50kg.

[0136] 4. Cathodic stripping resistance: The test method in SY / T4113.3-2019 is adopted, and the parameters of 65℃, -1.5V, and 28d are used to test the coating's cathodic stripping resistance.

[0137] The test results are shown in Tables 1 and 2.

[0138] Table 1 Test data results of the embodiments and comparative examples

[0139]

[0140]

[0141] Table 2. Comparison of test results of different embodiments

[0142]

[0143] From the test data shown in Table 1 above, it can be seen that: compared with Example 1, Example 1 only uses the base powder consistent with Example 1 in Example 1, resulting in poor wear resistance and scratch resistance of the overall coating; compared with Example 2, Example 2 only uses the intermediate powder consistent with Example 1. Although the component A in the intermediate powder is consistent with the base powder, the content is low, so the adhesion and cathode stripping resistance between the steel pipe are poor, and the intermediate powder does not contain the wear and scratch resistance components contained in the flour, so its wear resistance and scratch resistance are poor. Compared with Example 1 and Comparative Example 3, Comparative Example 3 only uses flour. Since the flour contains maleic anhydride grafted polyethylene, it has a certain adhesion to the steel pipe, but the overall adhesion and cathode stripping resistance are poor. Compared with Example 1 and Comparative Example 4, Comparative Example 4 only uses base powder and flour, lacks the transition of intermediate powder, resulting in poor adhesion between the base powder and flour, further affecting the cathode stripping resistance of the base powder. Compared with Example 5, Example 1 shows that only component B is used in the intermediate powder of Example 5, which results in poor bonding strength between the intermediate powder and the base powder, further affecting the poor resistance to cathodic stripping. Compared with Example 6, Example 2 shows that the base powder in Example 6 lacks phenolic modified epoxy resin, which results in poor bonding between the base powder and the steel pipe, further affecting the poor resistance to cathodic stripping. Compared with Example 7, Example 7 lacks isocyanate modified epoxy resin, which also results in poor bonding between the base powder and the steel pipe, further affecting the poor resistance to cathodic stripping. Compared with Example 8, Example 8 lacks polyvinyl butyral, which also results in poor bonding between the base powder and the steel pipe, further affecting the poor resistance to cathodic stripping. Compared with Example 9, Example 9 lacks nano-silicon dioxide, affecting the poor resistance to cathodic stripping of the base powder. From the data analysis of Table 2, it can be seen that compared with Example 2, the content of polytetrafluoroethylene in the flour in Example 2 is increased, which improves the wear resistance and scratch resistance of the coating, among which the wear resistance is more prominent. Compared with Example 1 and Example 3, the content of ultra-high molecular weight polyethylene in the flour in Example 3 is increased, which improves the wear resistance and scratch resistance of the coating, among which the scratch resistance is more prominent. It shows that the addition of polytetrafluoroethylene and ultra-high molecular weight polyethylene in flour can play a synergistic role in greatly improving the wear resistance and scratch resistance of the coating. It can be seen from the data of Example 1, Example 2, and Example 3 that the anti-corrosion powder material in the present invention has very excellent adhesion and cathode stripping resistance with the steel pipe, and the anti-corrosion material flour has excellent wear resistance and scratch resistance. In the process of transporting seawater, it can reduce the corrosion caused by sediment scouring in seawater, and further extend the service life of the steel pipe.

[0144] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A powder coating for anti-corrosion steel pipes for conveying seawater, characterized in that: include: Base powder, middle powder and flour; The base powder is composed of the following raw materials in parts by weight: 20-30 parts of bisphenol A epoxy resin, 20-30 parts of phenolic epoxy resin, 5-10 parts of isocyanate modified epoxy resin, 15-25 parts of phenolic curing agent, 2-5 parts of polyvinyl butyral, 0.5-2 parts of accelerator, 0.5-2 parts of coupling agent, 0.5-2 parts of nano silicon dioxide, 10-20 parts of color filler, 0.5-1 parts of leveling agent, and 0.5-1 parts of defoaming agent; The intermediate powder is a mixture of two components A and B, wherein component A is the base powder, and component B is composed of the following raw materials in parts by weight: 50-70 parts of maleic anhydride grafted polyethylene, 5-15 parts of maleic anhydride grafted polyethylene wax, 5-15 parts of polyvinyl butyral, and 0.5-1 part of defoaming agent; The flour is composed of the following raw materials in parts by weight: 30-60 parts of maleic anhydride grafted polyethylene, 5-10 parts of ultra-high molecular weight polyethylene, 5-10 parts of maleic anhydride grafted polyethylene wax, 1-10 parts of a compatibilizer, 10-20 parts of polytetrafluoroethylene, 10-20 parts of fused silica powder, 1-5 parts of a pigment, and 0.2-1 parts of an antioxidant.

2. The powder coating for anticorrosive steel pipe for conveying seawater according to claim 1, characterized in that: The particle size of the base powder is 60 meshes to 180 meshes.

3. The powder coating for anticorrosive steel pipe for conveying seawater according to claim 1, characterized in that: The accelerator is selected from at least one of 2-methylimidazole and 2-isopropylimidazole; Or, the coupling agent is a powder coupling agent containing epoxy groups; Or, the pigment filler is at least one selected from titanium dioxide, phthalocyanine blue, phthalocyanine green, medium chrome yellow, DPP red, permanent red, permanent violet, ultramarine, nano barium sulfate, nano calcium carbonate, nano silicon powder, nano wollastonite powder, nano feldspar powder, and mica powder; Or, the leveling agent is an acrylic leveling agent; Or, the defoaming agent is a benzoin product.

4. The powder coating for anticorrosive steel pipe for conveying seawater according to claim 1, characterized in that: The particle size of the B component is 60 meshes to 100 meshes.

5. The powder coating for anticorrosive steel pipe for conveying seawater according to claim 1, characterized in that: The mass ratio of the component A to the component B is 1:1-1.

5.

6. The powder coating for anticorrosive steel pipe for conveying seawater according to claim 1, characterized in that: The compatibilizer is tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer resin; Or, the pigment is at least one selected from carbon black, titanium dioxide, phthalocyanine blue, phthalocyanine green, medium chrome yellow, DPP red, permanent red, permanent violet, and ultramarine; Alternatively, the antioxidant is selected from at least one of antioxidant 215, antioxidant 1010, and antioxidant 168.

7. The powder coating for anticorrosive steel pipe for conveying seawater according to claim 1, characterized in that: The particle size of the flour is 40 meshes to 100 meshes.

8. A method for preparing a powder coating for an anticorrosive steel pipe for conveying seawater according to any one of claims 1 to 7, characterized in that: include: The raw materials of the base powder are mixed evenly, extruded by twin screws, crushed by tableting, ground, and sieved to obtain the base powder; The raw materials of component B are mixed evenly, extruded by twin screws, cooled, and pelletized; the pellets are low-temperature cooled, and the cooled pellets are ground into powder by ultra-low temperature grinding process, and sieved to obtain intermediate powder component B; Mix component A and component B evenly to obtain intermediate powder; Mix all the raw materials of flour evenly, extrude with twin screws, cool and pelletize underwater; The granular material is low-temperature cooled, and the cooled granules are ground into powder by ultra-low temperature grinding process, and then sieved to obtain flour.

9. A coating process for a powder coating for an anticorrosive steel pipe for conveying seawater according to any one of claims 1 to 7, characterized in that: include: The steel pipe is preheated and derusted, then heated to rotate, and the base powder and the intermediate powder are sprayed on the inner and outer walls of the steel pipe in sequence. The steel pipe is placed in a heating furnace for melting while being kept in a rotating state, and then the steel pipe is taken out and flour is sprayed on the intermediate powder. Finally, the steel pipe is placed in a heating furnace for secondary heating while being kept in a rotating state, and then taken out and cooled naturally to obtain the product.

10. Use of the powder coating according to any one of claims 1 to 7 in the field of marine engineering.

Citation Information

Patent Citations

  • Phenolic epoxy powder coating for anticorrosion in seawater desalination pipeline, and preparation method thereof

    CN110205000A

  • Composite anti-corrosion and anti-fouling treatment process for marine facilities, coating and preparation method

    CN113845844A

  • A kind of anticorrosive powder material resistant to seawater corrosion and its preparation method and application

    CN116716020B

Cited By

  • Powder coating for anticorrosion steel pipe for conveying seawater and preparation method and application thereof

    CN122609133A